OVERNIGHT COST ESTIMATION OFINDONESIA’S COGENERATION POWER PLANT FOR INDUSTRIAL PROCESSES - Rizki Firmansyah Setya Budi; Arum Puni Rijanti; Sahala M. Lumbanraja; Elok S. Amitayani; Moch. Djoko Birmano; Edwaren Liun (Jurnal Pengembangan Energi Nuklir, 2018)
Indonesia’s cogeneration power plant for industrial processes (PeLUIt) is needed to be implemented in Indonesia. Economic analysis is an important factor for PeLUIt implementation. One of the data that needs in the analysis is overnight cost. This research estimates HTGR’s overnight cost by using scaling law.By using the estimated value, it can be calculated the PeLUIt overnight cost. The research’s purpose is to obtain an estimation of overnight costs of PeLUIt. The estimation result shows the overnight cost of PeLUIt. PeLUIt 10 MWth has an overnight cost 166,26 million USD. PeLUIt 30 MWth has an overnight cost 233,49 million USD. PeLUIt 50 MWth has an overnight cost 281,31 million USD. PeLUIt 100 MWth has an overnight cost 371,86 million USD. PeLUIt 350 MWth has an overnight cost 657,16 million USD.Keywords: PeLUIt; Estimation; High temperature gas-cooled reactor; Overnight cost; Scaling law